# Difference between revisions of "1962 AHSME Problems/Problem 3"

(→Solution) |
(→Solution) |
||

Line 10: | Line 10: | ||

Substituting gives us <math>(2x+3)-2=(x+1)\implies 2x+1=x+1\implies x=0</math>. | Substituting gives us <math>(2x+3)-2=(x+1)\implies 2x+1=x+1\implies x=0</math>. | ||

− | Therefore, our answer is <math>\boxed{\textbf{(B)}\ 0 | + | Therefore, our answer is <math>\boxed{\textbf{(B)}\ 0}</math>; |

## Revision as of 00:07, 10 November 2013

## Problem

The first three terms of an arithmetic progression are , in the order shown. The value of is:

## Solution

Let represent the common difference between the terms. We have .

Substituting gives us .

Therefore, our answer is ;